How do tax-based revitalisation policies affect urban property development? Evidence from Bronzeville, Chicago. (April 2022) - Kim, Minjee
Fiscal incentives are frequently used to stimulate property development in distressed communities but the efficacy and impacts of this approach have been contested. In this study, a theory of real estate production was utilised to evaluate the Opportunity Zones (OZ) policy in the USA. Qualitative data collected from interviews and fieldwork are analysed to understand how the property development scene of a predominantly African-American neighbourhood had been affected by the OZ designation. Interviewees, including black local developers, represented diverse types and scales of real estate production. It was found that new investment capital was flowing into Bronzeville but not into projects proposed by small, local developers and community organisations. This was largely for two reasons: first, the less experienced and resource-constrained players had insufficient resources and expertise to connect with the OZ-induced investors. Second, when they were connected, their projects were deemed highly risky and thus unattractive. The perception of risk was likely amplified in Bronzeville, a historically marginalised black neighbourhood. For tax-based urban revitalisation policies to increase marginalised communities' access to capital, appropriate public interventions must be accompanied to level out the playing field for the under-resourced and historically marginalised players of real estate production. One such intervention might be to create and support a network of financial intermediaries that specialise in connecting capital to projects proposed by black developers, other non-profit developers and community organisations. Without such measures, policies such as OZ are likely to exacerbate existing inequalities rather than uplifting disadvantaged communities.